2015
DOI: 10.1108/ijopm-11-2013-0479
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making towards achieving world-class total productive maintenance

Abstract: Purpose – World-class total productive maintenance (TPM) status depends on critical success factors (CSF) to be properly implemented. The relevant literature has identified several CSF; however, researchers have not investigated the degree of importance of each phase of the process. The purpose of this paper is to prioritize the CSFs that influence TPM implementation during each phase of the process in order to aid decision making in companies. Design/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 61 publications
(71 reference statements)
0
23
0
Order By: Relevance
“…The important thing is to find out key metrics for the assessment of performance indicators of the program. Piehnicki et al (2015) investigate priority of critical success factors for implementing TPM properly.…”
Section: Problem Of the Definition And Literature Review On Tpmmentioning
confidence: 99%
“…The important thing is to find out key metrics for the assessment of performance indicators of the program. Piehnicki et al (2015) investigate priority of critical success factors for implementing TPM properly.…”
Section: Problem Of the Definition And Literature Review On Tpmmentioning
confidence: 99%
“…Copeland (Piechnicki et al, 2015), evidential reasoning theory (ERT) (Yan et al, 2012), genetic algorithm (GA) (Aguilar-Lasserre et al, 2009), geometric mean (Piechnicki et al, 2015), grey relational analysis (GRA) (Samvedi et al, 2012;Pitcchipoo et al, 2013), the Kano model (Ghorbani et al, 2013), life cycle assessment (LCA) (Chan et al, 2013), preference ranking organization method for enrichment evaluations (PROMETHEE) (Rao and Patel, 2010;Avikal et al, 2014), scoring methods (Sun et al, 2008), a technique for order preference by similarity to ideal solution (TOPSIS) (Büyüközkan et al, 2008;Ghorbani et al, 2013;Samvedi et al, 2013;Kilic et al, 2014;Yayla, 2015;Dincer et al, 2016), and VIKOR (Ren and Lützen, 2015).…”
Section: Integrated Ahp and Multiple Approachesmentioning
confidence: 99%
“…In their research, Piechnicki, et al [26] identified a set of critical TPM success factors and grouped them into eight categories: education and training, teamwork, planning and preparation, senior managerial commitment, resistance to change, change of culture, employee involvement, monitoring results, and effective communication; as can be seen, there are a lot of CSF human resources for TPM. However, Hernández Gómez et al [27] classified three categories for CSF: strategic planning, technical aspects, and human resources development.…”
Section: Critical Success Factors Of Tpmmentioning
confidence: 99%
“…TPM implementation [4,26,27] proper education and training of maintenance staff. follow-up and control of the maintenance program.…”
Section: Latent Variable Itemsmentioning
confidence: 99%
See 1 more Smart Citation